Sheep in the Tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
'Sheep Production in the Tropics' by A. B. Carles Oxford University Press (1983) ISBN 0 18 859 449 6 £ 16.00 (hardback) ISBN 0 19 859 485 2 £ 5.95 (paperback)